T-bet regulates differentiation of forkhead box protein 3+ regulatory T cells in programmed cell death-1-deficient mice. (2nd January 2015) - Tahara, M; Kondo, Y; Yokosawa, M; Tsuboi, H; Takahashi, S; Shibayama, S; Matsumoto, I; Sumida, T
Summary: Programmed cell death-1 (PD-1) plays an important role in peripheral T cell tolerance, but whether or not it affects the differentiation of helper T cell subsets remains elusive. Here we describe the importance of PD-1 in the control of T helper type 1 (Th1) cell activation and development of forkhead box protein 3 (FoxP3 + ) regulatory T cells (Tregs ). PD-1-deficient T cell-specific T-bet transgenic (P/T) mice showed growth retardation, and the majority died within 10 weeks. P/T mice showed T-bet over-expression, increased interferon (IFN)-γ production by CD4 + T cells and significantly low FoxP3 + Treg cell percentage. P/T mice developed systemic inflammation, which was probably induced by augmented Th1 response and low FoxP3 + Treg count. The study identified a unique, previously undescribed role for PD-1 in Th1 and Treg differentiation, with potential implication in the development of Th1 cell-targeted therapy.